The human centred approach to bionanotechnology in telemedicine: ethical considerations - Costa, Gonçalo Jorge Morais da (2014)
The information and communication technologies (ICTs) field is expanding rapidly and affecting several domains of mankind, as for example healthcare. Therefore, ICTs can act as an enabler or a provider these fields through telemedicine. Consequently, promoting an human centred and ethical approach is the primary challenge concerning ICT healthcare innovation. Simultaneously, can we deter- or at least discourage- innovation that serves malicious ends, or that causes serious threats to humanity? So, the purpose of this contribution is to discuss the relationship between ICT evolution and healthcare, particularly concerning a specific correlated research fields: bionanotechnology and telemedicine. For that, we will focus in its applications, and sort of ethical and moral dilemmas encompasses.